Deteksi Dini Risiko Sindrom Metabolik pada Remaja di Daerah Urban dan Rural: Early Detection of Metabolic Syndrome Risk in Adolescents in Urban and Rural Areas - Aisyah, Riandini; Jatmiko, Safari Wahyu; Bestari, Rochmadina Suci; Supraba, Intan Pratiwi; Utami, Indari; Wibowo, Haryo Kunto; Mapa, Anna Rochim; Utami, Aurelia Ratna; Anggitaratri, Zakia Novi; Haliza, Sheli Nur; Fitri, Alifah Aulia; Anam, Ilham Hafizha Maulana; Azenta, Moch. Tabriz; Syahida, Safira; Sulistiyo, Azka Hafiy; Brilliantama, Fandy Akbar; Maulida, Amira Hasna; Wafiq, Muhammad Azzim; Kamila, Aulida Azkia; Rohman, Raihan Fadzlur (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Metabolic syndrome is a collection of metabolic disorders that are closely related to an increased risk of developing diabetes mellitus and cardiovascular diseases in obese adolescents. Metabolic syndrome in adolescents is still reversible with varying timeframes. In adolescents with metabolic syndrome, the transition from homeostasis with normal blood sugar levels to type 2 diabetes occurs more rapidly compared to adults. Early diagnosis of metabolic syndrome is essential for prevention through lifestyle changes. Living in urban areas has a higher risk of obesity compared to living in rural areas after controlling for other variables. This activity aims to initially screen metabolic syndrome in middle school adolescents in urban and rural areas. The measurement of metabolic syndrome parameters involved 107 students, consisting of 47 middle school students in urban areas and 60 in rural areas. The measurement and data analysis results showed significant differences in body mass index (p<0,001), waist size (p=0.03), waist circumference (p=0.007), and upper arm circumference (p=0.002) between students in urban and rural areas, while blood sugar levels, blood pressure, and neck circumference did not show significant differences.